Molecular identification of natural hybridization between Melastoma malabathricum and Melastoama beccarianum in Sarawak, Malaysia. Issue 10 (15th April 2019) - Wu, Renzhi; Zou, Peishan; Tan, Guangwen; Hu, Zhenyang; Wang, Yongqi; Ning, Zulin; Wu, Wei; Liu, Ying; He, Shaoyun; Zhou, Renchao
Abstract: Hybridization is very common in flowering plants and it plays a significant role in plant evolution and adaptation. Melastoma L. (Melastomataceae) comprises about 80–90 species in tropical Asia and Oceania, among which 41 species occur in Borneo. Natural hybridization is frequently reported in Melastoma in China, but so far there have been no confirmed cases of hybridization in Southeast Asia (including Borneo), where most species occur. Here, we identified a case of natural hybridization between Melastoma malabathricum L. and Melastoma beccarianum Cogn. in Sarawak, Malaysia, by using sequence data of three nuclear genes and one chloroplast intergenic spacer. Melastoma malabathricum is the most widespread species of this genus, occurring in almost the whole range of this genus, while M. beccarianum is a local species endemic to northern Borneo. Our results showed that natural hybridization and introgression occur between M. malabathricum and M. beccarianum, and the introgression was asymmetrical, mainly from M. malabathricum to M. beccarianum . As adaptive traits can be transferred by introgression, our study suggests that natural hybridization should be a significant mechanism for the evolution and adaptation of Melastoma in Southeast Asia. However, introgression from the common species M. malabathricum to the relatively rare species M. beccarianum may cause the decline of M. beccarianum, incurring conservation concern. With a large number of species of Melastoma and almost year‐around flowering in Southeast Asia, more cases of natural hybridization are expected to be found and identified in near future. Abstract : The plant genus Melastoma had been evoked through rapid radiation. Natural hybridization may be an important mechanism for generating high species diversity in Southeast Asia. We provided compelling molecular evidence for natural hybridization between M. malabathricum and M. beccarianum, with the latter as a local species endemic to Borneo. We also detected asymmetrical introgression from M. malabathricum to the endemic species, incurring the conservation concern.